The Administration Educational School by 3 SMARTs THEPHA Model Fight Covid of Thepha School - Pisuttipan, Banjob (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2022)
The objectives of this research were 1) to study the condition, problems and needs of management in Thepha School in the situation of COVID-19, 2) to develop a 3 SMARTs THEPHA Model Fight Covid institute management model of Thepha School and 3) to assess the success of Thepha School's 3 SMARTs THEPHA Model Fight Covid institute management model, the research process consisted of 4 steps: 1) studying the current condition, management problems and needs school management model 3 SMART THEPHA Model Fight Covid is brainstorming, these are Thepha School working group of 71 people and the school basic education committee of 15 people, 2) develop a model of educational institution management in the form of the Thepha Model to fight COVID by having 5 qualified persons to check the suitability of the study. and a feasibility assessment form of the educational institution administration model, 3) an analysis of the results of the implementation of the 3 SMARTs THEPHA Model Fight Covid school management model, the informants were 1 deputy director of academic affairs and 71 working groups responsible for school operations, and 4) evaluated the results of the school management model 3 SMARTs THEPHA Model Fight Covid by the informants, Including the basic education committee of 15 people, working group of 71 people, students of 1,085 people and parents of students 1,085 people, and a total of 2,170 people, analyze the data for content and compile it into an essay. The Results of the research were as follows: Current condition Problems and needs in school administration found that the management in terms of policy and implementation of national policies in educational institutions for the readiness of educational management teacher and teaching management parents on the student side, in the situation of the COVID-19 epidemic, there is a condition of management that must be Finding a way to implement the quality of education in all dimensions. The development of the school management model under the 3SMARTs THEPHA Model Fight Covid has the following results: 1) THEPHA Model 2) 3SMARTs from the analysis of problems and needs, SMART director is the smartness of SMART executives, teacher is the teacher's smart SMART student is the student's smart the operation is under PDCA quality management. The assessment of the results of the school management model using 3SMARTs THEPHA Model Fight Covid found that 3.1 O-net test scores of Mathayom 3 students in the 2020 academic year have a higher development value than the 2019 academic year for all and some subjects higher than the national level. 3.2 The implementation of the school management model 3SMARTs THEPHA Model Fight Covid found that the students' satisfaction parents of the school board and teachers and personnel in preparing to fight COVID with technology in all aspects at the best to the best level.